2017
DOI: 10.1080/09540105.2017.1332006
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory evaluation of black rice extract inhibits TNF-α, IFN-γ and IL-6 cytokines produced by immunocompetent cells

Abstract: Black rice has been known for its many beneficial effects to our body because it contains several chemical compounds that act as antiinflammatory agents. This study aims to compare the antiinflammatory activity of ethanol extract and aqueous extract of black rice. Anti-inflammatory activity test was performed in vitro on splenocytes of diabetes mellitus mice model as the control of inflammation. Cells were cultured in Roswell Park Memorial Institute medium with 10% fetal bovine serum, anti-CD3 and lipopolysacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…The possible mechanism of this suppression may be mediated by downregulating the gene expression of NF-κβ and decreasing the phosphorylation of Iκβα and Iκββ by quercetin, thus suggesting that quercetin decreases the activation of NF-κβ [25]. Anthocyanins, the other active compound of HSL, have antioxidant, anti-inflammation, and anti-cancer properties [26]. Anthocyanins inhibit the production of nitric oxide, prostaglandine E2, TNF-α, and IL-6 in a dose-dependent manner without a cytotoxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanism of this suppression may be mediated by downregulating the gene expression of NF-κβ and decreasing the phosphorylation of Iκβα and Iκββ by quercetin, thus suggesting that quercetin decreases the activation of NF-κβ [25]. Anthocyanins, the other active compound of HSL, have antioxidant, anti-inflammation, and anti-cancer properties [26]. Anthocyanins inhibit the production of nitric oxide, prostaglandine E2, TNF-α, and IL-6 in a dose-dependent manner without a cytotoxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The nutritive potential of this fruit is well justified due to the high content of polyphenols, especially anthocyanins and polyunsaturated fatty acids (Rufino et al, 2010). Anthocyanins can stimulate the activity of immunocompetent cells, capture free radicals directly, repair DNA and repair damaged cells (Hartati, Widjanarko, Widyaningsih, & Rifa'i, 2017). Studies have shown that anthocyanins have a high antioxidant capacity and activate important pathways in the fight against metabolic reactors, which highlights its importance in the fight against cellular oxidation and consequently in the pathogenesis of cardiovascular diseases, hepatic diseases, diabetes and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Cytokines that are induced by NF-κB, particularly, IL-6 and IL-1β, can also directly activate the NF-κB pathway, thus establishing a positive auto regulatory loop that can augment the inflammatory response (Mantovani, Allavena, Sica, & Balkwill, 2008;Peng et al, 2019). Previous studies showed that ACNs have antiinflammatory activity by inhibiting the release of inflammatory cytokines such as IL-6, TNF-α and IL-1β (Freitas et al, 2018;Hartati, Widjanarko, Widyaningsih, & Rifa'i, 2017). Data from this study shown that the anti-inflammatory effect of BAE might be associated with diminished NF-κB expression in light-induced retina damage.…”
Section: Discussionmentioning
confidence: 99%